The Relationship between Oral Health Perception, Oral Health Literacy and Oral Health Behaviors among Dental Service Recipients, Trang Hospital, Trang Province, Thailand - Masamae, Sabina; Buenae, Zulfa; Boonchu, Puttipong; Sriprang, Chavanakorn; Mudchiew, Thanarat (The Journal of Chulabhorn Royal Academy, 2025)
This cross-sectional descriptive study aimed to investigate personal information, oral health perception, oral health literacy, oral health care behaviors, and factors associated with oral health care behaviors among dental service users at Trang Hospital. A total of 340 participants were selected from dental service recipients using accidental sampling. Data were collected using a self-administered questionnaire during June-July 2024. Data analysis was performed using descriptive statistics and inferential statistics, including the Chi-square test and Spearman rank correlation coefficient at a significance level of 0.05. Study results showed that the majority of participants were female, with an average age of 33.37±12.39 years. Approximately 81.76% had previously received oral health education. Overall oral health literacy across six domains was rated at a moderate level (mean score: 104.88±17.26). Toothbrushing behavior was rated at a high level (mean score 4.05±0.60), while the use of additional oral hygiene adjuncts was rated at a moderate level (mean score 3.17±0.82). Factors significantly associated with toothbrushing behavior (p-value < 0.05) included gender, perceived satisfaction with oral health, having received oral health education, and overall oral health literacy. Specific domains of oral health literacy found to be significantly associated with toothbrushing behavior were: access to health information and services, knowledge and understanding, communication skills for enhancing expertise, and self-management skills. Factors significantly associated with the use of additional oral hygiene adjuncts (p-value < 0.05) included: education level, perceived satisfaction with oral health, and 5 of oral health literacy domains which are the access to health information and services, knowledge and understanding, communication skills for enhancing expertise, self-management skills, and decision-making skills. Therefore, programs or activities should be implemented to enhance oral health literacy, with a focus on improving access to health information, developing understanding, and strengthening communication skills. These efforts will help the working-age population effectively manage their oral health care